Determination Of Hydrophilic Phenolic Compounds In Palm Oil And Palm Kernel Oil - Abdullah, Fadzlina (2009)

(untitled)
The quantification of total phenolic content expressed as gallic acid equivalent (GAE) was based on the Folin-Ciocalteau colorimetric method. The total phenolic contents (TPC) of palm oil samples were determined from crude to refined palm and palm kernel oils obtained from palm oil mills. The samples was crude palm oil (CPO), refined palm oil (RPO), refined palm olein (RPOo), crude palm kernel oil (CPKO), refined palm kernel oil (RPKO), and palm kernel olein (PKOo). All samples were utilized to determine the TPC. Quantification of phenolics extracted from palm and palm kernel oils showed the highest level of TPC in CPO and refining reduces the TPC in the oil. The TPC in CPO ranged from 31.73 – 70.18 mg/kg, bleached palm oil (BPO) from 18.36 – 22.25 mg/kg, RPO from 16.90 – 26.89 mg/kg, RPOo from 11.36 – 12.20 mg/kg and palm fatty acid distilled (PFAD) from 1.07 – 5.48 mg/kg. While that the TPC for CPKO ranged from 16.80 –27.25 mg/kg, RPKO from 3.16 – 3.82 mg/kg and PKOo from 2.52 – 8.60 mg/kg. Furthermore, the reduction of phenolic content were obtained in the different stages of the refining step.